Impact of audit quality and digital transformation on innovation efficiency: Role of financial risk-taking - Yunis, Manal (2024)
Advances in digital technologies, platforms, and infrastructures drive digital transformation, which significantly influences firm strategies, processes, and innovation efforts. This study investigates the impact of digital transformation and audit quality on the innovation efficiency of Chinese firms, focusing on firms' risk-taking behavior. Analyzing data from 2007 to 2021, we find that digital transformation substantially enhances innovation efficiency, especially in smaller firms and those experiencing slow growth during economic downturns. Furthermore, our research underscores the importance of audit quality in promoting innovation efficiency, going beyond traditional financial reporting. However, the study also reveals that although digital transformation and high audit quality are essential for boosting efficiency, excessive risk-taking negatively affects this relationship. The impact of digital transformation and audit quality on innovation efficiency is further moderated by several factors such as firm size, business cycle, and growth. These findings hold significant implications for investors and policymakers, emphasizing the importance of integrated governance and digital strategies in optimizing innovation outcomes.